Green Processing using Alternative Supercritical Fluids - Knez Hrnčič, M.; Knez, Ž. (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
In the scientific literature, contributions about supercritical fluid phase equilibria mostly discuss systems with conventional supercritical fluids, especially supercritical CO2. In the present work, investigation of non-conventional supercritical fluids was taken into consideration. Solubility of pure vanillin and ortho-ethyl vanillin in argon was measured at temperatures of 40°C, 60°C and 80°C and at pressures up to 500 bar. Maximal solubility of vanillin was obtained at a temperature of 40°C and a pressure of 438 bar, at approximately 0.015 g/g. For ortho-ethyl vanillin, highest solubility was attained at pressures above 300 bar at lower temperatures, about 0.5 g/g. The content of vanillin was determined after extraction of vanilla pods with argon and CO2. Despite mass yields higher than 50% in conventional extraction, the content of vanillin in extracts obtained by supercritical extraction is higher, clearly demonstrating that supercritical fluids are more selective solvents for vanillins than conventional ones.